2020
DOI: 10.1016/j.jmig.2019.09.791
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after Surgery for Colorectal Endometriosis: A Systematic Review and Meta-analysis

Abstract: The recurrence rate after colorectal surgery for endometriosis is up to 50% at 5 years. The aim of the current review and meta-analysis was to assess recurrence associated with shaving, disc excision, and segmental resection for endometriosis with colorectal involvement. Data Sources: A systematic review was performed by searching the PubMed, ClinicalTrials.gov, EMBASE, Cochrane Library, and Web of Science databases for publications before February 28, 2019, using the terms "colorectal endometriosis" and "recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 60 publications
(95 reference statements)
1
16
0
Order By: Relevance
“…A relevant data is the recurrence rate that we observed, allowing us to say that 3.5 women in 10 who underwent surgical treatment presented new endometriotic lesions. This value is similar to those obtained by other authors, with recurrence rates ranging from 25% to 43% 4,13,14,17 . More important than numbers, is the analysis of risk factors for the resurgence of the disease to guide the post‐surgical management.…”
Section: Discussionsupporting
confidence: 89%
“…A relevant data is the recurrence rate that we observed, allowing us to say that 3.5 women in 10 who underwent surgical treatment presented new endometriotic lesions. This value is similar to those obtained by other authors, with recurrence rates ranging from 25% to 43% 4,13,14,17 . More important than numbers, is the analysis of risk factors for the resurgence of the disease to guide the post‐surgical management.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies demonstrated the efficacy of bowel surgery for endometriosis on the basis of a low rate of symptomatic and anatomic recurrence [17]. However, colorectal surgery for RSE is associated with a significant morbidity, eventually requiring additional interventional procedures and drastically reducing the quality of life of the affected patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with segmental resection, superficial resection has the benefits of technical simplicity, shorter operative times, lower complication rates, shorter hospitalization times, and better functional results in terms of continence and constipation (37) . The main disadvantage of the technique, as reported in a recent systematic revision and meta-analysis, is an increased recurrence rate in comparison with segmental resection (chance rate [OR] 5.53; P=0.001) and with discoid resection (OR 3.83, P=0.01) (45) .…”
Section: Superficial Resection (Shaving)mentioning
confidence: 99%
“…A recent systematic review about histology-verified recurrence at least 12 months after intestinal endometriosis surgery covered 41 studies and selected four for the meta-analysis. According to the authors, the risk of recurrence was significantly lower in segmental or discoid resection when compared to superficial resection (45) . Histopathologic findings, such as the presence of satellite lesions, marginal positivity, and thickness of infiltration, seem to have no relation to recurrence rates or to impact on quality of life (62) .…”
mentioning
confidence: 99%
See 1 more Smart Citation